Diferenciando o espaço e produzindo cidades: lógicas e agentes da produção do espaço urbano em Ribeirão Preto/SP e Londrina/PR - Abreu, Marlon Altavini de [UNESP] (2014)
Working with data of real estate ads from 1995 to 2010, among several other sources of information, this research puts in a comparative perspective the characteristics of real estate markets of two medium-sized cities. Looking up to apprehend processes that are common between them and others, particular to each one, looking for comprehend some of the contemporaneous traces of their production and of their conditions of consumption. Being guided by the historical dynamics of their spatial formation, it considers, in the wide process of reproduction of capitalists' relations, an scenery of changing in the economic, social and political contents, that intertwine and combine to those cities morphology. If in one side we watch the redefinition of logical of urban space production generally and the cities particularly, confronting characteristics such as the continuity of urban tissues and amplifying the dynamics of inner differentiation of the city, in the other side, under the particularity of real state production, we watch redefinitions of strategies of agents' performance and the extension of the power applied to their practical in producing and appropriating of the cities...